Employment Act 1955 (Amendment) 2022 - Md Radzi, Mohd Shahril Nizam (Kanun: Jurnal Undang-undang Malaysia; Vol 35 No 2 (2023): Kanun: Jurnal Undang-undang Malaysia Volume 35 Number 2 July 2023, 2023)
- Full text: PDF